100 likes | 202 Views
Serial Number: 44. y = cosx. 1. -2 π. - π. π. 2 π. 1-. G(x)=f(x) + 1. 2. 1. -2 π. - π. π. 2 π. 1-. G(x)=f(x) - 1. 1. -2 π. - π. π. 2 π. 1-. 2-. G(x)=f(2x). 1. - π. - π /2 . π /2. π. -1. G(x)=2f(x). 2. -2 π. - π. π. 2 π. -2. G(x)=f(x- π/ 4). 1. -9 π /4.
E N D
y = cosx 1 -2π -π π 2π 1-
G(x)=f(x) + 1 2 1 -2π -π π 2π 1-
G(x)=f(x) - 1 1 -2π -π π 2π 1- 2-
G(x)=f(2x) 1 -π -π/2 π/2 π -1
G(x)=2f(x) 2 -2π -π π 2π -2
G(x)=f(x-π/4) 1 -9π/4 -5π/4 -π/4 π/4 5π/4 9π/4 1-
G(x)=f(x+π/4) 1 -9π/4 -5π/4 -π/4 π/4 5π/4 9π/4 1-
G(x)=f(-x) 1 -2π -π π 2π 1-
(g(x)=-f(x 1 -2π -π π 2π 1-